2022
DOI: 10.1155/2022/1787854
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Treatment Combining Antiangiogenesis with Chemoradiotherapy Impinges on the Peripheral Circulation Vascular Endothelial Cells and Therapeutic Effect in the Patients with Locally Advanced Nasopharyngeal Carcinoma

Abstract: This study was implemented for the evaluation on the circulating endothelial cells’ (CECs) clinical significance in the locally advanced nasopharyngeal carcinoma treatment with endostatin-combined chemoradiotherapy. This study enrolled 47 patients with locally advanced nasopharyngeal carcinoma who were hospitalized from May 9, 2012 to March 10, 2013. These patients were split up into the observation group (25 patients) and control group (22 patients). Patients in the observation group received the endostatin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Recent evidence shows that patients with nasopharyngeal carcinoma undergoing treatment with chemotherapy (docetaxel þ cisplatin) and an angiogenesis inhibitor (endostatin) experience a significant reduction in CEC numbers compared with those receiving chemotherapy alone [56]. This reduction is also evident during everolimus treatment in advanced pancreatic neuroendocrine tumours, supporting everolimus's role in inhibiting angiogenesis [57].…”
Section: Circulating Endothelial Cells and Chemotherapy-induced Vascu...mentioning
confidence: 99%
“…Recent evidence shows that patients with nasopharyngeal carcinoma undergoing treatment with chemotherapy (docetaxel þ cisplatin) and an angiogenesis inhibitor (endostatin) experience a significant reduction in CEC numbers compared with those receiving chemotherapy alone [56]. This reduction is also evident during everolimus treatment in advanced pancreatic neuroendocrine tumours, supporting everolimus's role in inhibiting angiogenesis [57].…”
Section: Circulating Endothelial Cells and Chemotherapy-induced Vascu...mentioning
confidence: 99%
“…Endostar significantly enhances radiosensitivity in NPC, reducing the side effects of radiotherapy. Moreover, it can be combined with chemotherapy or chemoradiotherapy to improve the prognosis of patients with metastatic NPC (101,103,104). The effect of endostar is related to the downregulation of VEGF expression (105) and could correct the pathological angiogenesis process to disrupt the hypoxic environment in tumor tissues (106).…”
Section: Angiogenesis-related Therapy In Npcmentioning
confidence: 99%
“…This therapy can be used for the treatment of locally advanced and metastatic NPC ( 98 100 ). Recent studies have demonstrated that Endostar, a recombinant human endostatin, is a targeted drug with antiangiogenic and antitumor effects, and when combined with other antitumor therapies, it significantly enhances the overall anticancer effect ( 101 , 102 ). Endostar significantly enhances radiosensitivity in NPC, reducing the side effects of radiotherapy.…”
Section: Angiogenic Application In Npcmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%